Evaluasi Kesesuaian Lahan Komoditas Pangan Utama di Kecamatan Umbu Ratu Nggay Barat Kabupaten Sumba Tengah - Marten Umbu Nganji; Bistok Hasiholan Simanjuntak; Suprihati Suprihati (agriTECH, 2018)
This research was conducted in West Umbu Ratu Nggay district of Central Sumba Region in January–March 2017. The method of analysis used was LQ (Location Quotient) method, matching method and overlay method. The results showed that the maim food commodities in West Umbu Ratu Nggay District were green beans with values of LQ 1,60; sweet potato with LQ 1,33, rice with LQ 1,16; and corn with LQ 1,03. Green beans suitability class is S2 (moderatelly suitable) with area 28.021,13 ha (99.69%) and N (not suitable) with area 87.91 ha (0.31%). Sweet potato commodity with land suitability is in class S1 (highly suitable) with area 90,41 ha (0.32%), S2 (moderatelly suitable) with of 27.930,73 ha (99.7%), and N (not suitable) with area 87,91 ha (0.31%). Commodity of rice with land suitability class S1 (highly suitable) with area of 1.322,43 ha (4.70%), S2 (moderatelly suitable) with area of 26.704,21 ha (95.00%), and N (not suitable) with area of 83,24 ha (0.30%). Corn commodity with land suitability class S2 (moderatelly suitable) with area of 8.21,13 ha (99.69%) and N (not suitable) with area of 87,91 ha (0.31%). ABSTRAKPenelitian ini dilakukan di Kecamatan Umbu Ratu Nggay Barat Kabupaten Sumba Tengah pada bulan Januari-Maret 2017. Metode analisis yang digunakan adalah metode LQ (Location Quotient), metode pencocokan dan metode overlay. Hasil analisis menunjukkan bahwa komoditas pangan unggulan di Kecamatan Umbu Ratu Nggay Barat secara berturut-turut adalah kacang hijau dengan nilai LQ 1,60, ubi jalar dengan nilai LQ 1,33, padi sawah dengan nilai LQ 1,03 dan jagung dengan Nilai LQ 1,03. Kelas kesesuaian lahan kacang hijau adalah S2 (cukup sesuai) dengan luas 28.021,13 ha (99,69%) dan  N (tidak sesuai) 87,91 ha (0,31%). Komodias ubi jalar  dengan kelas kesesuaian lahan S1 (sangat sesuai) dengan luas 90, 41 ha (0,32%), S2 (cukup sesuai) dengan luas 27.930,73 ha (99,37%), dan N (tidak sesuai) 87,91 ha (0,31%). Komoditas padi sawah dengan kelas kesesuaian lahan S1 (sangat sesuai) 1.322, 43 ha (4,70%). S2 (cukup sesuai) 26.704,21 ha (95,00%), dan N (tidak sesuai) 83,24 ha (0,30%). Komoditas jagung dengan kelas kesesuaian lahan S2 (cukup sesuai) 28.021,13 ha (99,69%) dan N (tidak sesuai) 87,91 ha (0,31%).